Left Main Atresia: Supply from the right coronary circulation- a rare coronary artery anomaly - Prajapati, Dipanker; Sharma, Deewakar; KC, Man Bahadur; Sharma, Jyotindra; Sharma, Umesh C (Nepalese Heart Journal, 2022)
Coronary artery anomalies are rare incidental findings, about 20% with clinical significance of possible increased risk of related adverse cardiac events including sudden death. Multi detector computed tomography has become the first-line imaging modality to visualize the origin and course of anomalous blood vessels, assisting the further categorization and treatment recommendations. We present a case of 52 years old woman with left main atresia and right coronary artery supplying the entire cardiac muscles through the connection of posterior lateral artery to the distal segment of the left circumflex artery.